2014
DOI: 10.1167/iovs.14-13995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduced Retinal VLC-PUFA on Rod and Cone Photoreceptors

Abstract: The VLC-PUFAs are important for rod, but not cone, function and for rod photoreceptor longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 27 publications
2
61
1
Order By: Relevance
“…Despite the minimal decrease in VLC-PUFAs, Harkewicz et al (2012) found that Elovl4 C-cKO mice had decreased cone flicker responses at 7 months of age compared to WT mice. These results are contrary to Barabas et al (2013) and Bennett et al (2014b), who did not find cone dysfunction at 6 and 12 months, respectively.…”
Section: Comparison Of Mouse Modelscontrasting
confidence: 99%
See 4 more Smart Citations
“…Despite the minimal decrease in VLC-PUFAs, Harkewicz et al (2012) found that Elovl4 C-cKO mice had decreased cone flicker responses at 7 months of age compared to WT mice. These results are contrary to Barabas et al (2013) and Bennett et al (2014b), who did not find cone dysfunction at 6 and 12 months, respectively.…”
Section: Comparison Of Mouse Modelscontrasting
confidence: 99%
“…This is obviated when the reduction of retinal VLC-PUFAs are considered (Table 20.1). These fatty acids were decreased by 36-97 % of WT values in the R-cKO and RC-cKO mice (Harkewicz et al 2012;Barabas et al 2013;Bennett et al 2014b;Marchette et al 2014). The VLC-PUFA levels in the cone-specific Elovl4 ablated mice (C-cKO) were unaffected (Table 20.1), but this could be due to the fact that mice are rod-dominant and that these fatty acids comprise only 12 % of the total fatty acids in the retina (Rotstein and Aveldano 1988).…”
Section: Comparison Of Mouse Modelsmentioning
confidence: 90%
See 3 more Smart Citations